Pengaruh Sistem Pengendalian Internal dan Good Government Governance terhadap Pencegahan Fraud Pengelolaan Dana Desa : (Studi pada Pemerintahan Desa Pakuan Ratu Kab.Way Kanan) - Anesya Freni Livia; Nursalma Nursalma; Meita Sekar Sari (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
This research aim to analyze the influence of internal control system and good government governance toward village funds fraud prevention management in pakuan ratu sub-district way kanan regency. In this research, the researcher used quantitative method by using primary data which is questionnaire. The population that the researcher used was all of the village government officials in 3 districts in pakuan ratu sub-district, way kanan regency. the sample that the researcher used is saturated sampling technique and there were 57 village government officials. the technique to analyze the data by using validity test, reliability test, double linier regression and classic assumption test with SPSS 23 version. The result of this research shows that internal control system makes significantly good effect toward village funds fraud prevention and good government governance.